KNOWLEDGE AND PERCEPTION OF UNDERGRADUATE MEDICAL AND NURSING STUDENTS OF UNIVERSITI MALAYSIA SARAWAK TOWARDS UTILISATION OF SOCIAL MEDIA AS LEARNING TOOL IN PHYSIOLOGY EDUCATION - Mak, Xin Yun; Mohamad Danisy, Abdul Razak; Nur Zulaikha, Lailee; Ting Chee Hong, Tie; Marlynna, Sarkawi; Saiful Bahri, Talip; Norhida, Ramli; Asheila, Meramat (FMHS, UNIMAS, 2024)
Background and objective: Human physiology is essential for all medical field professionals, providing crucial knowledge relatable to clinical conditions. Nowadays, alternative methods for learning physiology including social media platforms, are available with the evolution of technology. Therefore, this study aims to investigate the knowledge, perception and engagement of social media usage in physiology learning among pre-clinical medical and nursing undergraduates at a public university in Malaysia. Method: This quantitative cross-sectional study involved 230 pre-clinical medical and nursing students of Universiti Malaysia Sarawak (UNIMAS), with 204 fully consented respondents in the final analysis. The online modified questionnaire was distributed to analyse the social media knowledge (Perceived Social Media Literacy, PSML), perception (Social Networking Usage, SNUQ) and level of engagement (Online Student Engagement, OSE) in physiology learning. Statistical analysis was performed to evaluate the outcome. The study outcomes were compared between undergraduate pre-clinical medical and nursing students using Mann-Whitney U test. Result: Overall, 61.7% pre-clinical medical students and 38.3% of nursing students responded to the questionnaire. The PSML mean score showed 83.46 (SD=18.26) with a significant difference between medical and nursing students in the informational awareness dimension (U=3280.00, p=0.001). Despite showing a significant difference between the courses of study in perceived ease of use (U =3654.00, p=0.02), SNUQ revealed the lowest score for the overall perceived social media usage score (M=3.91, SD= 1.02). The OSE result showed moderate positive engagement to social media with M=3.74. Conclusion: UNIMAS undergraduate medical and nursing students exhibit average knowledge and perception of social media as a learning tool in physiology education. The findings suggest that UNIMAS students, especially medical students, are well-prepared to use social media for physiology learning.